COMPARATIVE EMIC-ETIC REVIEW OF ZHANG DE AND TROMPENAARS’S CORPORATE CULTURE - Assoc. Prof. Dr. Lee Kar Ling; Jing Chunqi (International Journal of Accounting, Finance and Business, 2021)
The paper focused on a literature review of organizational culture by analyzing thedifferent dimensions between Western and Chinese organizational culture to ascertain whetherthere are similarities or differences using an emic-etic approach. The purpose of selecting acomparative review of Western and Chinese organization culture is due to the rise of China asan economic power house whereby more and more companies are beginning to query whethera Western or Chinese organization culture would better serve the organization given today’sglobal landscape. This study focuses on Trompenaars cultural dimensions as a representationof the Western organization culture as the cultural model is considered to be the mostcomprehensive as compared to other Western organization culture and China’s Zhangde’sdimensions of organizational culture since the latter’s organization cultural dimensions aredistinctly Chinese in nature. Applied emic-etic research method combined with the specificcultural items of organizational culture between Western and China adopted as the researchmethodology. Such a methodology is qualitative in nature to determine whether a revised formof organizational culture model suitable for both the Western world and China’s company ispossible for global companies investing in Asia and the Western world.